Bipartite Graph Algorithm With Reference Frame Representation For Protein Tertiary Structure Matching - Othman, Fazilah (2010)
Proteins with structural resemblances tend to share similarities in biological functions. Protein dengan kesamaan struktur cenderung berkongsi fungsi biologi yang sama.